Balanced scorecard evolution : a dynamic approach to strategy execution - Niven, Paul R. (Hoboken, New Jersey : Wiley, 2014)
"The best plan is useless without effective executionThe future of business has become so unpredictable that your five-year plan may be irrelevant next week. To succeed in the modern market, you must constantly assess your progress and adapt on the fly. Agility, flexibility, continual learning, and adaptation are the new rules of business success. A differentiating strategy is crucial, but it will only lead to competitive advantage if you execute it flawlessly. You'll succeed only if you have the right insight for strategic planning and the agility to execute your plan.Balanced Scorecard Evolution: A Dynamic Approach to Strategy Execution provides the latest theory and practice from strategic planning, change management, and strategy execution to ensure your business is flexible, future ready, and primed for exceptional execution. Author Paul R. Niven guides you through the new principles of The Balanced Scorecard and shows you how to apply them to your planning and strategy execution endeavors. Read case studies that illustrate the theory and practice of strategic agility and execution Learn how to create the objectives, measures, targets, and strategic initiatives that can make your plan a reality Use the latest change management techniques to boost strategy execution success Gain the knowledge and tools you need to face your challenges head-on Motivate your employees to change behaviors toward plan accommodation Making a plan isn't enough. You must actually take steps to implement your plan, and this requires excellent leadership skills. Change can be hard, and your organization may be resistant. Balanced Scorecard Evolution: A Dynamic Approach to Strategy Execution provides everything you need to make things happen"--
"Balanced Scorecard Evolution: A Dynamic Approach to Strategy Execution provides the latest theory and practice from strategic planning, change management, and strategy execution to ensure your business is flexible, future ready, and primed for exceptional execution. Author Paul R. Niven guides you through the new principles of The Balanced Scorecard and shows you how to apply them to your planning and strategy execution endeavors"--
Includes index.
Includes bibliographical references and index.
Description based on print version record and CIP data provided by publisher.
Keywords: Organizational effectiveness; Balanced scorecard (Management); Strategic planning; Organizational change; BUSINESS & ECONOMICS / Decision-Making & Problem Solving; Balanced scorecard (Management).; Organizational change; Organizational effectiveness; Strategic planning; Electronic books; Electronic books